2003
DOI: 10.1590/s0066-782x2003000400005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and nitric oxide inactivation in postmenopausal women

Abstract: Original ArticleCardiovascular diseases are less prevalent in premenopausal women and in those receiving hormone replacement therapy as compared with postmenopausal women and men 1 . This protective effect is attributed to estrogens, and one of the mechanisms of action may be related to the metabolism of plasma lipoproteins 2 .Estrogens reduce LDL-cholesterol and increase HDLcholesterol 3 . However, these changes in lipid profile only contribute to approximately 25% of the protective effect of estrogens 4 . Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…5). This basal NOx finding is consistent with the results of some recent studies (Nawate et al, 2005;Pereira et al, 2003). However, there are contradictory results regarding the effects of estrogen replacement on plasma NOx levels in postmenopausal women (Cagnacci et al, 2003;Khorram et al, 2002;Konukoglu et al, 2000).…”
Section: Possible Relationship Between Stress-induced Dbp Elevation Asupporting
confidence: 89%
“…5). This basal NOx finding is consistent with the results of some recent studies (Nawate et al, 2005;Pereira et al, 2003). However, there are contradictory results regarding the effects of estrogen replacement on plasma NOx levels in postmenopausal women (Cagnacci et al, 2003;Khorram et al, 2002;Konukoglu et al, 2000).…”
Section: Possible Relationship Between Stress-induced Dbp Elevation Asupporting
confidence: 89%
“…One of the factors compromising estrogen effects in aging might be an increased oxidative stress in the vascular tissue. A study by Pereira et al has demonstrated an increase in proinflammatory nitrotyrosine levels in plasma following menopause (46). Similar changes in the vascular tissue may adversely affect the nongenomic protective pathways elicited through ERa, with a loss of estrogen-mediated beneficial effects on the vasculature (47).…”
Section: Estrogen and Agingmentioning
confidence: 97%
“…The lower production of NO was related to either reduced availability of NO synthase or inactivation of NO by the reaction of superoxide radical forming the peroxynitrite (ONOO -), which is a strong oxidizing agent. The peroxynitrite and its decomposition products induce peroxidation of the membrane lipids, causing endothelial lesions and an increase in vascular permeability [39]. Kanazawa et al [40] demonstrated that dietary LOOH generated alkylperoxyl radical (LOO -) after its reaction with various heme compounds such as myoglobin, cytochrome c, hemin, and hematin.…”
Section: Endogenously Produced Lipid Oxidation Productsmentioning
confidence: 99%